‘Bottom-up securitization’: A visual turn in security studies - M. A. Kucherov; M. V. Kharkevich (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the digital age, images have pervaded almost all spheres of public life and politics. International relations are no exception. The visual dimension of world politics attracts increasing attention which resulted in the emergence of the so-called visual turn in the theory of international relations. It gained particular prominence within the framework of constructivism and particularly within one of the central and most widespread constructivist theories, i.e. the securitization theory. The first section of the paper examines the concept of ‘visual turn’. The second section considers the current state of art of the securitization theory. The third section outlines key features and possible implications of ‘visual securitization’ to the study of international relations. To this end, the authors refer to a resonant case of a Syrian migrant boy Aylan Kurdi, who died in 2015 while trying to immigrate to Europe. The fourth section examines some limitations of the ‘visual securitization’ theory. The authors conclude that the ‘visual turn’ has led to a certain democratization of securitization practices by opening up new opportunities for the ‘bottom-up securitization’, or ‘people’s securitization’. Thus, it questions the traditional monopoly of political elites on the molding of a security narrative. At the same time, the ‘visual turn’ extends the list of possible reference objects of securitization, which comes to include not only domestic audiences, but also other communities. As a result, ‘visual securitization’ raises a number of new issues. In contrast to a traditional ‘speech act’, an image can be open to various interpretations and as such would make the process of interaction with the audience too complicated and inconsistent. The possibility of incorrect interpretation places increased demands on the communicative context and hinders the use of an image as an independent securitization tool. The authors argue that the key to addressing these issues lies in a more active use of artificial intelligence technologies and social networks.